Perception and (In)Direct Experience of Sexual Harassment and Blackmail in the Academic Context: the Perspective of Female Students (Croatian Sociological Review, 2024)
Research on sexual harassment and blackmail in contemporary Serbia is recent. Previous studies show  these issues occur in various situations. However, the university context has seldom been analysed, despite evident power hierarchy. As female students constitute a particularly vulnerable group, this paper explores their perceptions and (in)direct experiences of sexual harassment and blackmail, as well as their expectations regarding institutional responses. The analysis is based on the results of two focus group discussions involving 22 female students from all study levels at the Faculty of Philosophy and the Faculty of Sport and Physical Education at the University of Novi Sad. The results revealed the sensitivity of female students to sexual harassment and blackmail, accompanied by a degree of self-censorship when discussing the mentioned problem, especially with parents or other adults in their primary environment. Additionally, a continuity of (in)direct exposure of female students to sexual harassment and blackmail in both academic and nonacademic context has been observed. The students expect the faculty and university to respond to instances of sexual harassment and blackmail. Simultaneously, a portion of them believes that the institutional response should extend beyond the faculty, even beyond the academic context, to provide additional protection for victims. A crucial aspect of the institutional response highlighted is the need for systematic education on this issue, targeting both students and all university staff. The research confirmed the complexity and multi-layered nature of the problem, and can serve as inspiration for further analyses of sexual harassment and blackmail in academic contexts.